The problem of the role of proverbs in the event of a speech act (Eurasian Journal of Learning and Academic Teaching, 2022)
This article discusses the concept of a speech act, its study, the views of world and Uzbek scientists on it, types and classification of speech act, in which the question of the pragmatic possibilities of proverbs is considered on the basis of comparison, description, classification of available sources.